1992
DOI: 10.1093/ajcn/55.2.461
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic advantages of spreading the nutrient load: effects of increased meal frequency in non-insulin-dependent diabetes

Abstract: The acute effect of increasing meal frequency as a model of slow absorption was studied for 1 d in 11 patients with non-insulin-dependent diabetes. On 1 d they took 13 snacks (the nibbling diet) and on another day the same diet was taken as three meals and one snack (the three-meal diet). The nibbling diet reduced mean blood glucose, serum insulin, and C peptide concentrations over the 9.5 h of observation and 24-h urinary C peptide output by 12.7 +/- 3.7% (mean +/- SE) (P = 0.0062), 20.1 +/- 5.8% (P = 0.0108)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
79
0
4

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(88 citation statements)
references
References 27 publications
5
79
0
4
Order By: Relevance
“…Our experimental protocol, by administering frequent small meals, spread carbohydrate absorption throughout the 9 h study period. This procedure partially reproduces the effects of soluble ®bers to delay and lengthen carbohydrate absorption time, and have been shown to decrease average plasma glucose and insulin concentrations observed over 24 h in both healthy individuals and type 2 diabetic patients (Jenkins et al, 1989(Jenkins et al, , 1992. The main observation of our study is the loss of postprandial reduction in glucose and insulin concentrations after partitioning a b-glucan containing meal.…”
Section: Resultsmentioning
confidence: 75%
“…Our experimental protocol, by administering frequent small meals, spread carbohydrate absorption throughout the 9 h study period. This procedure partially reproduces the effects of soluble ®bers to delay and lengthen carbohydrate absorption time, and have been shown to decrease average plasma glucose and insulin concentrations observed over 24 h in both healthy individuals and type 2 diabetic patients (Jenkins et al, 1989(Jenkins et al, , 1992. The main observation of our study is the loss of postprandial reduction in glucose and insulin concentrations after partitioning a b-glucan containing meal.…”
Section: Resultsmentioning
confidence: 75%
“…42 In addition to weight control, a further argument against the nibbling theory is that no consistent pattern was found between snacking/intake frequency and metabolic variables, which is in contrast to previous studies. 2,10,43 A limitation in our study is that our obese subjects were volunteers for an intervention study and may thus not be representative for all obese subjects, but rather for men and women seeking help for obesity. Moreover, like most other studies, our study is cross-sectional and thus we cannot conclude causality.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been shown that neither fat nor protein in the amounts found in most foods (with the exception of peanuts and most nuts) Lower postprandial glucose rise (Jenkins et al, 1990(Jenkins et al, ,1992Bertelsen et al, 1993;Jones et al, 1993) Reduced daily mean insulin levels (Jenkins et al, 1990(Jenkins et al, ,1992Bertelsen et al, 1993;Jones et al, 1993) Flatter gastric inhibitory polypeptide response (Jenkins et al, 1990(Jenkins et al, ,1992Bertelsen et al, 1993) Decreased 24 h urinary C-peptide output (Jenkins et al, 1989(Jenkins et al, ,1992 Prolonged suppression of plasma free fatty acids (Jenkins et al, 1990) Reduced urinary catecholamine output (Jenkins et al, 1990) Lower total and LDL cholesterol levels (Jenkins et al, 1989Arnold et al, 1993;Cohn 1964) Reduced hepatic cholesterol synthesis (Jones et al, 1993) Decreased serum apolipoprotein B levels (Jenkins et al, 1989) Decreased serum uric acid levels Raised urinary uric acid excretion Adapted from Jenkins et al (1995). Glycemic index in chronic disease LS Augustin et al significantly alters the glycemic response (Wolever et al, 1994).…”
Section: Glycemic Index and The Slow-release Carbohydratementioning
confidence: 99%
“…Increasing meal frequency in isocaloric diets in diabetic and non-diabetic subjects has been shown to reduce postprandial glucose rise (Jenkins et al, 1992, Bertelsen et al, 1993Jones et al, 1993), daily insulin levels (Jenkins et al, 1992;Bertelsen et al, 1993;Jones et al, 1993) and 24 h urinary C-peptide output (Jenkins et al, 1989(Jenkins et al, ,1992. Increasing meal frequency is now included in the recommendations given for the management of diabetes by the American Diabetes Association (1994).…”
Section: Glycemic Index In Chronic Diseasementioning
confidence: 99%